2008
DOI: 10.1523/jneurosci.1673-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Backpropagating Action Potentials Trigger Dendritic Release of BDNF during Spontaneous Network Activity

Abstract: Brain-derived neurotrophic factor (BDNF) is a major regulator of activity-dependent synapse development and plasticity. Because BDNF is a secreted protein, it has been proposed that BDNF is released from target neurons in an activity-dependent manner. However, direct evidence for postsynaptic release of BDNF triggered by ongoing network activity is still lacking. Here we transfected cultures of dissociated hippocampal neurons with green fluorescent protein (GFP)-tagged BDNF and combined whole-cell recording, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
156
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 118 publications
(167 citation statements)
references
References 46 publications
11
156
0
Order By: Relevance
“…After transfection, the cultures were incubated at 30°C in 5% CO 2 . Immunostaining confirmed that BDNF-GFP is targeted to the dendrite and packed into secretory granules of the regulated pathway of secretion (Kuczewski et al, 2008b).…”
Section: Methodsmentioning
confidence: 78%
See 4 more Smart Citations
“…After transfection, the cultures were incubated at 30°C in 5% CO 2 . Immunostaining confirmed that BDNF-GFP is targeted to the dendrite and packed into secretory granules of the regulated pathway of secretion (Kuczewski et al, 2008b).…”
Section: Methodsmentioning
confidence: 78%
“…Neurons from postnatal day 0 rat hippocampus were dissociated using trypsin and plated on coverslips coated with polyethylenimine as previously described (Kuczewski et al, 2008b). Eleven days after plating, neurons were transfected with cDNAs coding for BDNF-GFP (gift from Dr. V. Lessmann, Institute of Physiology, Otto-von-Guericke University Magdeburg, Magdeburg, Germany) according to the OZ Biosciences protocol (Buerli et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations